Penerapan Metode Vikor dalam Penilaian Objek Wisata kota Bengkulu - Septianto, Muhamad Diecky; Elfianty, Lena; Sartika, Devi (MEANS (Media Informasi Analisa dan Sistem), 2022)
The Tourism Office of Bengkulu Province is a government agency engaged in tourism, especially Bengkulu Province which supports activities related to tourism activities such as recording tourist objects, evaluating tourism objects and introducing tourism objects to tourists. All this time, the evaluation process for tourism objects has not been carried out optimally, therefore it cannot be known with certainty which tourism objects need to be addressed and which need to be improved. This is because the evaluation carried out is only limited to collecting data on tourism objects. The implementation of the Vikor Method in the assessment of tourism objects in Bengkulu City is done by building an application that can identify the results of the application of the Vikor method using the Visual Basic .Net programming language and SQL Server 2008r2 database. There are 11 (eleven) criteria used in the assessment of tourism objects attractions in Bengkulu City, namely natural beauty, coolness, cleanliness, security, entertainment, shopping, health services, communication networks, power sources, transportation, tour guides. The assessment was carried out on 6 tourist objects, namely Fort Malborough, Soekarno's House, Fatmawati's House, Bengkulu Museum, Panjang Beach and Dendam Tak Sudah Lake by assigning a value to 11 predetermined criteria. From the results of the assessment, it will be reprocessed into the Vikor Method to find out which tourism objects has the lowest Vikor index value sorted by rank. Based on the results of the Black Box Method testing on the tourism objects assessment application in Bengkulu City, it can be concluded that the functionality of the application has been running properly and is able to display the final results of the assessment based on the Vikor Method